Predictors of Cochlear Implantation Outcomes in Children with Auditory Neuropathy Spectrum Disorders - Jafari, Zahra (Université d'Ottawa / University of Ottawa, 2023)
Introduction: Auditory neuropathy spectrum disorder (ANSD) is a disorder characterized by impaired temporal coding of acoustic signals due to a deficiency in neural synchrony or neural transmission. Despite variations in speech perception outcomes within both patients and studies, current evidence demonstrates that children with ANSD, who use hearing aids (HAs) or cochlear implants (CIs), generally achieve speech perception performance comparable to peers with sensorineural hearing loss (SNHL). However, limited studies have reported factors that have prognostic value for auditory intervention outcomes. The objectives of this doctoral thesis, consisting of three consecutive associated projects on children with ANSD, were (1) to determine factors with predictive value for post-intervention (CIs and/or HAs) outcomes through a retrospective study, (2) to systematically summarize and critically appraise existing evidence of the prognostic value of early auditory electrophysiologic tests and MRI findings for CI outcomes through a systematic review (SR), and (3) to systematically overview, summarize, and critically appraise evidence of CI outcomes through an umbrella review of current SRs (overview of SRs). -- Methods: For the first project, the records of 38 children with ANSD between 5 and 18 years old, 63.20% males, who used CIs (71%) and/or HAs, identified at the Children's Hospital of Eastern Ontario (CHEO) were reviewed. For the second and third projects, the SRs were guided by the PRISMA 2020 statement, and electronic databases were searched without restrictions on language, publication status, or year of publication. In the second project, studies on children with ANSD (including those with cochlear nerve deficiency [CND]), cochleovestibular nerve (CVN) abnormalities, or SNHL reporting the relevance of preoperative and/or postoperative electric compound action potential (eCAP), electric auditory brainstem response (eABR), and/or MRI results to CI outcomes were included. The methodological quality and strength of evidence were assessed using the Crowe Critical Appraisal Tool (CCAT) and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) tool, respectively. In the third project, all SRs that reported CI outcomes in children with ANSD were included. The methodological quality of the selected SRs was evaluated using the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2) checklist, and the risk of bias in evidence was assessed using the Risk of Bias in Systematic Reviews (ROBIS) tool. -- Results: In the retrospective chart review (first project), ages at HL diagnosis and CI activation and the length of follow-up with CI/HA showed a significant relationship with open-set speech perception outcomes (i.e., the scores of Phonetically Balanced Kindergarten [PBK] test with word and phoneme speech materials and Hearing in Noise Test [HINT] in quiet and noise conditions). Using a Forward Linear Multiple Regression Model, the length of follow-up with CI/HA and bilateral amplification showed prognostic value for speech perception performance. In the second project, 25 papers were included in the review. While it was difficult to draw a firm conclusion about the eCAP findings, current evidence strongly supports the prognostic value of eABR and MRI for post-CI speech perception outcomes. According to the eight SRs selected for the third project, children with ANSD achieve CI outcomes comparable to their peers with SNHL. However, in children with postsynaptic ANSD (i.e., those with CND), cochlear nerve hypoplasia is associated with better speech recognition outcomes compared to cochlear nerve aplasia, especially in the absence of additional disabilities and/or medical comorbidities (ADs/MCs). -- Conclusion: Children with ANSD, especially those without cochlear nerve aplasia and ADs/MCs, achieve speech perception outcomes comparable to their peers with SNHL. In addition, age at HL diagnosis, age at CI activation, the length of follow-up with CI/HA, bilateral amplification, and eABR and MRI findings are associated with or have predictive value for intervention outcomes. The findings of the SRs should be interpreted with caution given the low quality of evidence and risk of bias in the studies selected for SRs.
Keywords: Auditory neuropathy spectrum disorder; Cochlear nerve deficiency; Cochlear implant; Hearing aid; Speech perception; Follow-up period; Electric compound action potential; Electric auditory brainstem response; Magnetic resonance imaging; Prognostic value; Predictor; Outcome